2018
DOI: 10.1016/j.jiph.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Microfilaria in kidney biopsy: A report of two cases

Abstract: Filariasis is traditionally diagnosed on finding microfilaria in peripheral blood smear and in cases of occult filariasis by immunological tests. Clinically, it presents with a wide range of symptoms and signs. We present two cases of filariasis presenting with renal symptoms warranting kidney biopsy. Histopathology of both revealed microfilaria in the glomerular capillary loop. First case was a 23-year-old male who presented with complaints of passage of milky urine. Second case was a 36-year-old female patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In our study, two dogs had high serum creatinine levels (8 and 2.99 mg/dL). Although kidney is not a target organ for microfilarial infection, some reports have shown proteinuria and hematuria as common findings [ 47 , 48 ]. In the case of creatinine, it has been reported that creatinine levels increase due to microfilarial infection in humans and canines [ 49 , 50 ], which may be caused by kidney dysfunction and intravascular hemolysis associated with infection as well as immune-mediated glomerular damage, mainly in chronic infection [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, two dogs had high serum creatinine levels (8 and 2.99 mg/dL). Although kidney is not a target organ for microfilarial infection, some reports have shown proteinuria and hematuria as common findings [ 47 , 48 ]. In the case of creatinine, it has been reported that creatinine levels increase due to microfilarial infection in humans and canines [ 49 , 50 ], which may be caused by kidney dysfunction and intravascular hemolysis associated with infection as well as immune-mediated glomerular damage, mainly in chronic infection [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microfilariae in the intestine are rarely observed, this infection observed in S. niger is particularly localized and of low intensity, unlike infection by W. bancrofti and Loa loa in humans, causing intestinal hemorrhages, ulceration, and allergic reactions 7 . Kidney lesions with microfilariae had reduced capsular space, which may have led to a decrease in the glomerular filtrate, causing uremia and proteinuria as observed microfilariae in humans 8,9 . In humans microfilariae of W. bancrofti , L. loa , Dirofilaria inmitis , and Onchocerca volvulus have been identified in the central nervous system, inducing lesions such as gliosis, meningitis, and encephalitis, 10 which can result in nervous symptoms 11 …”
Section: Discussionmentioning
confidence: 99%
“…7 Kidney lesions with microfilariae had reduced capsular space, which may have led to a decrease in the glomerular filtrate, causing uremia and proteinuria as observed microfilariae in humans. 8,9 In humans microfilariae of W. bancrofti, L. loa, Dirofilaria inmitis, and Onchocerca volvulus have been identified in the central nervous system, inducing lesions such as gliosis, meningitis, and encephalitis, 10 which can result in nervous symptoms. 11 Filaria in neotropical primates belong to the genus Dipetalonema, which parasitizes the thoracic and abdominal cavities, and Mansonella (Tetrapetalonema), described as a parasite of subcutaneous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Renal involvement in microfilaremic carriers manifests as microscopic hematuria and proteinuria which can be attributed to two mechanisms: 1) mechanical damage to glomeruli leading to hematuria and 2) deposition of immune complexes. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%